DIVERSITY OF ENDOPHYTIC FUNGI FROM ACACIA NILOTICA LINN., AND SCREENING THEIR BIO-ACTIVITY AGAINST ORAL PATHOGENS - S.S.MEENAMBIGA,; K. RAJAGOPAL, (International Journal of Pharma and Bio Sciences, 2016)
Endophytic fungi diversity from the leaves and barks of Acacia nilotica used in treating oral diseases were studied during four different seasons for about one year. Four hundred bark and leaf segments were analyzed and a total of 553 isolates representing 17 taxa and 3 morphotypes were isolated. Aspergillus flavus was found to be dominant in all seasons and the frequency of endophytic fungi was found to be more in leaves than in bark tissues with some tissue-specific endophytes. Ethyl acetate extracts of endophytic fungi isolated from Acacia nilotica were screened against major oral pathogens such as Streptococccus mutans and Candida albicans by agar well diffusion method in Mueller- Hinton Agar media. The crude extract of Eupenicillium sp., isolated showed maximum zone of inhibition against S.mutans (18.67±0.36 mm) and C.albicans (16.3±0.36 mm) and the isolate Eupenicillium sp., from Acacia nilotica could be further explored for its activity against oral pathogens for novel secondary metabolite isolation.